Etnobotani Tumbuhan Obat Masyarakat Desa Lawe Cimanok Kabupaten Aceh Selatan: Ethnobotany of Medicinal Plants of the Lawe Cimanok Village Community, South Aceh Regency - Muslich Hidayat; Nusirwan Nusirwan (Universitas Negeri Semarang, 2025)
This ethnobotanical study aims to document the local knowledge of the Lawe Cimanok Village community in South Aceh regarding the use of medicinal plants. The methode used is a mixed methode with a Participatory Rural Appraisal (PRA) approach involving 30 selected respodents. The results of the study identified 60 species of medicinal plants from 37 families used by community. The analysis shows that leaves are the most commonly used part of the plant (57%), followe by fruit (13%) and rhizomes (10%). The most common processing methods are crushing and boiling, while the most common methods of use are drinking (46%), applying topically (11%), and applying as a poultice (33%). This study also revealed an inseparable spiritual aspect, where treatment is often accompanied by rituals and prayers. These findings represent a complex and holistic traditional knowledge system. However, this cultural heritage is highly vulnerable to exitinction as times change. Therefore, systematic documentation in this study is crucial for preservation efforts and as a database for the future development of herbal medicines based on local wisdom.